2021
DOI: 10.1049/rpg2.12088
|View full text |Cite
|
Sign up to set email alerts
|

Robust load frequency control for networked power system with renewable energy via fractional‐order global sliding mode control

Abstract: Owing to random load changes and transmission time delays in interconnected power systems with renewable energy, the load frequency control scheme has become one of the main methods to keep stability and security of power systems. To relieve communication burden and increase network utilisation, an adaptive event-triggered scheme is explored. Then, a new fractional-order global sliding mode control scheme comprising the fractional-order term in the sliding surface is adopted to improve robustness of load frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Because their stability index (W c ) is so large that their safety is lower than ours we have a small index in various parts that have been considered in the IEEJ WEST 10-machine model. Much of the work has been done in the past to illustrate the impact of communication delays [19][20][21], on the results obtained based on the impact on the feedback controller. Controllers need to be able to cope with communication delays, and how to reduce the risk of adverse effects should be addressed accordingly.…”
Section: General Results Achievedmentioning
confidence: 99%
See 2 more Smart Citations
“…Because their stability index (W c ) is so large that their safety is lower than ours we have a small index in various parts that have been considered in the IEEJ WEST 10-machine model. Much of the work has been done in the past to illustrate the impact of communication delays [19][20][21], on the results obtained based on the impact on the feedback controller. Controllers need to be able to cope with communication delays, and how to reduce the risk of adverse effects should be addressed accordingly.…”
Section: General Results Achievedmentioning
confidence: 99%
“…Heydari et al have shown that communication in delays affects microgrid island and continue with the second inspection that took place the survey was conducted with a small sample [19,20]. Some researchers showed one of the ways in which literature only assessed its power delayed check for the second check (e.g., [21]) and others (e.g., [22]) on the full line of the power of the system, both are small-scale signals. There are also indications of the effects of testing delays on the distribution system state estimation (DSSE) were investigated using Monte Carlo (MC) analysis in [23,24] are evaluated, using a well-defined weighted least squares (WLS) the weight of the matrix, in [25], however, to the knowledge of the authors, it has never been established as an undoubted source for growth the analytical expression for calculating the final state estimation (SE) is undoubtedly related to the shock from the communication.…”
Section: System Devicementioning
confidence: 99%
See 1 more Smart Citation
“…Sliding mode control, with its advantages in overcoming system uncertainties and achieving strong robustness against disturbances, has been widely used in a variety of fields [6][7][8]. System robustness is enhanced by combining dynamic surface control with the sliding mode [9][10][11][12]. It can be used in different systems such as nonlinear systems [13], Markovian jump systems [14], power systems, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The need and demand for making more accurate and precise calculations in many industrial and technological fields have caused fractional calculus to become very popular in recent years. Today, it is known that many physical processes in nature can be modeled by using fractional calculus, such as control systems [1,2], material modeling and mechanics [3,4], chaotic systems [5,6], power and energy systems [7,8] and medicine [9,10]. Due to the increasing growth in fractional order models in the various area of science, the analysis and the development of numerical methods for fractional differential equations (FDEs) and partial differential equations with time or space fractional derivatives have become an attractive area of research [11].…”
Section: Introductionmentioning
confidence: 99%